PENGARUH MEDIA SOSIAL TERHADAP KEHIDUPAN RELIGIUS MAHASISWA - Gule, Yosefo; Martauli, Elvin Desi; Ginting, Nurlia Br (JURNAL CURERE, 2023)
The internet is no longer just a complement to life; these are essential life-sustaining goods, thanks to more complex technology and faster data speeds. Quality Berastagi University students are no strangers to social media; they rely heavily on social media to fulfill their needs, and social media users imitate the actions of the influencers they follow, such as the way they dress, interact, believe, and think. The aim of the research is to find out how the influence of social media will have a positive impact or influence on the religious life of PGSD students in 2021. The research method used is quantitative, with numerical data processed using SPSS, and the population as well as the research sample is UQB students as many as 77 people. The data collection technique uses a questionnaire with a Likert scale as an assessment measuring tool, and the data analysis technique uses two techniques. Using simple linear regression and Oneway Anova. The results of the research show that there is an influence of social media on the religious life of PGSD UQB students class of 2021 as shown by the Siq value in the coefficient table of 0.000 - 0.05, and there is a positive influence of social media on religious life as shown by the t-coefficient table of 3.274. Ho was rejected but Ha agreed, meaning that social media (X) has a positive and quite large impact on religious life (Y). Social media has an impact of 18.7% on religious life, and other components that are not researched are 81.3%. YouTube has the greatest influence on the religious life of 2021 UQB PGSD students, with an average of 14.74 people choosing YouTube compared to other social media. These findings show that there is a need function that encourages participants to use YouTube compared to other social media to get the education, news or material they need with a more complete explanation of obtaining religious information.